The Uncertainties and Supply Chain Risk Management in Developing Country: An Empirical Investigation into Beverage Industry in Thailand Thitiya - Patarakosol, Thitiya (2011)
Nowadays there are high competitive pressures to perform in any type of business since there are trends of varieties of product types, short life cycle products, growing outsourcing and globalization of business. These factors result in increasing complexity of the supply chain network and a higher level of uncertainties and supply chain disruption risks. Thus, supply chain risk management is increasing in significance and is used to mitigate the risks that may occur. Also, previous studies of uncertainties and supply chain disruption risk were only considered in developed countries. There is not much research concerning a specific country or in a developing country. The differences in the context of culture, tradition, belief and infrastructure can change the perspectives of framework of supply chain disruption risks and risk management. Consequently, this research aims to investigate the turbulences and uncertainties that cause the overall supply chain disruption risks in the developing country, Thailand. This paper also proposes risk mitigation framework as the tool for risk management. It uses an empirical study with a survey of 253 feedbacks and the structural equation modelling to explore the demand uncertainty, quality uncertainty and logistics/distribution uncertainty impact on the magnitude and probability of supply chain disruption risk. Moreover, the finding shows that both magnitude and probability of supply chain disruption risk are important factors of the overall supply chain disruption risks. For the risk mitigation framework, the supply chain agility concept is adopted as the fundamental strategy for the firm to diminish the supply chain risk and enhance the overall organization performance. The result also shows that the organization practices - for example the supply chain integration and distribution flexibility - are also important as the antecedents of supply chain and distribution agility.